MQSUN baseline report: Impact evaluation of the DFID programme to accelerate improved nutrition for the extreme poor in Bangladesh, Phase II - Roy, Shalini; Barnett, Inka; Baxter, Ben; Gordon, Jessica; Hoddinott, John F.; Karachiwalla, Naureen; Naher, Firdousi; Tranchant, Jean-Pierre (International Food Policy Research Institute, 2015)
The DFID Programme to Accelerate Improved Nutrition for the Extreme Poor in Bangladesh aims to improve nutrition outcomes for children, mothers and adolescent girls by integrating the delivery of a number of nutrition-specific (or direct) interventions with the livelihood support provided to extremely poor people by three existing programmes in Bangladesh.